ILLOCUTIONARY ACTS ANALYSIS OF THE MAIN CHARACTER IN THE OPPENHEIMER MOVIE - Safira Fahroji (Intertwine: Journal of English Language, Literary, and Cultural Studies, 2025)
This research explored the role of speech acts within the context of pragmatics, focusing on their function in conveying meaning beyond literal expressions. By categorizing speech acts into locutionary, illocutionary, and perlocutionary acts, the study examined how each type contributes to communication. Searle’s four types of illocutionary acts, assertive, directive, commissive, and expressive. were analyzed to better understand the intentions behind the speaker’s utterances. The study specifically focused on illocutionary acts, demonstrating how these acts assist in interpreting the speaker’s intended message within a given context. Through a qualitative methodology and a descriptive approach, the research aimed to classify and examine the speech acts in the movie "Oppenheimer," revealing how the characters' dialogues represent real-life interactions and reflect the underlying pragmatic rules that guide communication. Keywords: Speech acts; Illocutionary; Movie.